2013
DOI: 10.1074/jbc.m113.500975
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Activation of the T-type CaV3.2 Channel

Abstract: Background:The low activation threshold of T-type Ca V 3.2 channels is central to neuronal rhythmogenesis. Results: The S4-S5 linker of Domain II is functionally coupled with Domains II and III during channel activation. Conclusion: Activation of Ca V 3.2 requires a specific interaction between adjacent domains. Significance: Disrupting this protein interface could be a pharmacological strategy to decrease Ca 2ϩ influx in neuronal pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…Each voltage-sensing domain is adjacent to the neighboring pore domain (e.g. see [35]), with the S4 of one domain forming hydrophobic interactions with the S5 of the adjacent domain (Fig. 1d).…”
Section: Architecture Of the Cav11 And Cav12 Channelmentioning
confidence: 99%
“…Each voltage-sensing domain is adjacent to the neighboring pore domain (e.g. see [35]), with the S4 of one domain forming hydrophobic interactions with the S5 of the adjacent domain (Fig. 1d).…”
Section: Architecture Of the Cav11 And Cav12 Channelmentioning
confidence: 99%
“…Indeed, LVA Ca 2+ channels contain a large conserved external loop (residues 211-336 for Ca V 3.1 channel) between the S5 transmembrane segment and the P pore loop of domain I [17], which is different in length with respect to the other three external loops and supports the pseudo-symmetry in LVA channels. At least two different reports have explored the role of pore-lining S6 segment residues in Ca V 1.2 and Ca V 3.2 channels [20,23]. The distal S6 transmembrane segment seems to be especially important for the voltage sensitivity of activation and the activation and deactivation kinetics of Ca V 1.2 channel; substitution of S6 pore region residues of domain I (IS6 L(434), domain II (IIS6; I781) or domain III (IIIS6; G1193) transformed the Ca V 1.2 from a HVA into a LVA Ca 2+ channel, probably for altering backbone-backbone helix interactions in a hydrophobic environment (reviewed in [20]).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Ca V 3.2 channels, the S4-S5 helix linker of domain II (IIS4-S5) interacts with the distal S6 pore region of domains II (IIS6) and III (IIIS6). In particular residues V907 and T911 of S4-S5 helix linker of domain II (IIS4-S5) interact with S6 of domains II (IIS6; I1013) and III (IIIS6; N1548) demonstrating that S4-S5 and S6 helices from adjacent domains are coupled in LVA Ca 2+ channels [23].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that IIS4 voltage sensor, with an important contribution of some residues from the S4-S5 linker, has the most dominant effect, followed by the IVS4 segment, in the low-voltage activation behavior of Ca V 3.3 channels. In this regard, a more recent study has shown that the activation of Ca V 3.2 channels might be the result of cooperative contribution of residues from the S4-S5 linker of Domain II and the S6 helices from Domains II and III [ 58 ]. In such a scenario, the results presented here for Ca V 3.3 channel might be due to the disruption of structural interactions between S4 voltage sensors, S4-S5 linkers, and S6 helices, that leads to the gating of the channel and, therefore, it can be anticipated that such interactions could be more relevant in the case of Domain II of Ca V 3.3 channels.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been shown in Ca V 3.2 channels that single and double mutations of residues in IIS4-S5 linker and IIIS6 helix led to a 25 mV negative shift in the steady-state inactivation curve [ 58 ]. Therefore, one possible explanation of our results in Ca V 3.3 channels could be that IS4 segment, the IS4-S5 linker or even the IS6 segment, have structural interactions with the “gating brake” structure localized in the I-II loop, and that the substitution of this voltage sensor with that of Ca V 1.2 does not restore such interactions leading the channels to inactive from closed states at very negative potentials.…”
Section: Discussionmentioning
confidence: 99%